Aqueous humour-induced lens epithelial cell proliferation requires FGF-signalling. (3rd September 2017) - Iyengar, Laxmi; Lovicu, Frank J.
Abstract: The eye lens grows by systematic proliferation of its epithelial cells and their differentiation into fibre cells. The anterior aqueous humour regulates lens epithelial cell proliferation whereas posteriorly, the vitreous stimulates lens fibre differentiation. Vitreous-derived members of the fibroblast growth factor (FGF) family induce fibre differentiation, with added support for FGFs as putative regulators of aqueous-induced lens cell proliferation. To further characterize this, given FGFs' known affinity for proteoglycans, we compared the effect of proteoglycan sulphation in growth factor- and aqueous-induced lens cell proliferation. Disruption of proteoglycan sulphation in lens cells specifically impacted on aqueous- and FGF-induced MAPK/ERK1/2-signalling, but not on that induced by other mitogens such as PDGF; however, cell proliferation was reduced in all treatment groups, regardless of the mitogen. Overall, by disrupting proteoglycan activity, we further highlight the significant role of FGFs in aqueous-induced ERK1/2 phosphorylation leading to lens cell proliferation.